The Right to Belong in School: A Critical, Transdisciplinary Conceptualization of School Belonging - Paul J. Kuttner (SAGE Publishing, 2023)
Belonging is a critical factor for supporting student success and well-being in school. Unfortunately, the work of fostering belonging at school for all students continues to face significant challenges. One reason is that the field of education is working from a limited conception of school belonging, based mainly in the discipline of psychology. Belonging is more than just a psychological sense-it is also a social, cultural, and even political process. In this article, Paul Kuttner explores six aspects of belonging that are underemphasized in the school belonging literature, arguing that we should think of school belonging as agentic, intersectional, systemic, political, place-based, and a right. Kuttner proposes a definition of belonging that encompasses these aspects and uses it to suggest future directions for research and practice.